A Quantitative Monitoring Study of Environmental Factors Activating Caihua and Wooden Heritage Cracks in the Palace Museum, Beijing, China - Xiang He; Hong Li; Yilun Liu; Binhao Wu; Mengmeng Cai; Xiangna Han; Hong Guo (Buildings)
Cultural heritage objects, including traditional Chinese polychrome paintings on architectures (Caihua) and wooden architectural components, frequently exhibit surface defects that are highly sensitive to environmental factors, resulting in progressive deterioration. However, due to limited data acquisition methods and quantitative analysis models, the stability and risks of defects such as cracks during environmental changes remain unclear. This study integrates photogrammetry and digital image processing to investigate through-cracks and craquelures on the surface of a well pavilion within the Palace Museum, Beijing. We confirmed the activity of these cracks, quantified crack widths, and studied the environmental influences on their development. Over a monitoring period of more than 15 months, the widths of seven cracks on four beams were measured alongside various environmental factors. Correlation analyses identified air humidity as the most significant factor influencing crack width fluctuations (p < 0.01). Numerical simulations revealed that short-term humidity exposure induces surface swelling and crack closure, whereas prolonged humidity leads to internal moisture transport and crack reopening. Furthermore, fitting parameters indicating the severity of crack variation correlated well with the degradation levels of the wooden components. In summary, this study establishes a monitoring and quantification procedure for assessing crack activity, explores the influence of humidity through numerical simulations, and identifies a potential indicator for the non-destructive assessment of timber component stability. The proposed framework offers an exploratory approach to addressing critical challenges in the health monitoring of wooden architectural components.